SOSIALISASI FISIOTERAPI SEBAGAI UPAYA PREVENTIF DAN KURATIF PADA KASUS OSTEOARTHRITIS GENU - Widnyana, M.; Putra, I.P.Y.P.; Utama, A.A.G.E.S. (Buletin Udayana Mengabdi, 2024)
Osteoarthritis (OA) genu is an aging disease of the knee joint that occurs due to damage to cartilage and narrowing of joint space. OA genu causes a decrease in functional ability and hinders productivity. People in Banjar Kabetan, Bakbakkan Village, Gianyar live from activities and have populations at risk of experiencing OA genu. The purpose of this service is to socialize the role of physiotherapy in preventive and curative efforts of OA genu cases. The specific target of this service activity is that the community is more familiar with physiotherapy and can do exercises as a preventive and curative effort for OA genu cases. The method used is to come directly to do a knee examination and education. The knee examination is carried out through a physical examination and the WOMAC (Western Ontario and Macmaster University) questionnaire. Education is carried out by the method of socializing pamphlets and simulating exercises. The service activity succeeded in presenting 100 participants. In the results of the knee examination, as many as 30 respondents experienced mild disability, 60 respondents experienced moderate disability and 10 respondents experienced severe disability. The average result of the disability score is 30.35+12.91, which means that residents experience moderate disability due to OA genu. The service participants were very enthusiastic, because through this program knee movement health improved, so that disability decreased and productivity could increase.